Carcinoma associated paraneoplastic peripheral neuropathies in patients with and without anti-onconeural antibodies. Issue 1 (1st July 1999) - Antoine, Jean-Christophe; Mosnier, Jean-François; Absi, Léna; Convers, Philippe; Honnorat, Jérôme; Michel, Daniel
Abstract : OBJECTIVE: When to suspect a paraneoplastic disorder is a puzzling problem that has not recently been studied in a large series of patients referred for peripheral neuropathy. METHODS: From 422 consecutive patients with peripheral neuropathy, 26 were analysed who concomitantly had carcinoma but no tumorous infiltration, drug toxicity, or cachexia. Their clinical, pathological, and electrophysiological data were analysed according to the presence of anti-onconeural antibodies, the latency between presentation and cancer diagnosis, and the incidence of carcinoma in the corresponding types of neuropathy of the population of 422 patients. RESULTS: Seven patients (group I) had anti-onconeural antibodies (six anti-Hu, one anti-CV2) and 19 did not (groups IIA and B). In group I, subacute sensory neuropathy (SSN) was the most frequent but other neuropathies including demyelinating neuropathies were present. Patients in group II A had a short latency (mean 7.88 months), and a rapidly and usually severe neuropathy which corresponded in 11/14 to an established inflammatory disorder including neuropathy with encephalomyelitis, mononeuritis multiplex, and acute or chronic inflammatory demyelinating polyneuropathy (CIDP). Patients in group IIB had a long latency (mean 8.4 years) and a very chronic disorder corresponding in four of five to an axonal non-inflammatory polyneuropathy. In this population, the incidence of carcinoma occurring with a short latency was 47% in sensory neuronopathy, 1.7% in Guillain-Barré syndrome, 10% in mononeuritis multiplex and CIDP, and 4.5% in axonal polyneuropathy. CONCLUSIONS: Paraneoplastic neuropathies associated with carcinoma are heterogeneous disorders. Neuropathies occurring with a long latency with tumours probably resulted from a coincidental association. Neuropathies which occurred within a few years of the tumour evolved rapidly and corresponded mostly to inflammatory disorders. As dysimmune neuropathies are probably paraneoplastic in a limited number of cases, patients with these disorders should probably not be investigated systematically for carcinoma in the absence of anti-onconeural antibodies, except when the neuropathy is associated with encephalomyelitis and probably with vasculitis. Questions remain concerning CIDP.